Global perspectives in policing and law enforcement - Mbuba, Jospeter M.; Appiahene-Gyamfi, Joseph; Baylis, Monika; Briskey, Mark F.; Christensen, Mikkel Jarle; Dai, Mengliang; Davies, Sharyn Graham; del Castillo, Federico; Fabini, Giulia; Grant, Lorna E. (Policing perspectives and challenges in the twenty-first century., 2021)
This book covers historical experiences, contemporary practices, and comparative perspectives of policing and law enforcement in various parts of the world to provide reliable literature on international and comparative policing.